# A CUBE MINUS B CUBE FORMULA

(a³ + b³) = (a + b)³ – 3ab(a + b)…………………………….(2)

Take the common term, then we get

(a³ + b³) = (a + b) <(a + b)2 – 3ab>…………………………..(3)

We know that

(a + b)2 = a² + 2ab + b²……………………….(4)

Substitute the equation (4) in equation (3).

(a³ + b³) = (a + b) <(a² + 2ab + b²) – 3ab>………………(5)

(a³ + b³) = (a + b)(a² – ab + b²)

Let us prove the above equation.

Consider a = 2 and b = 3. Substitute the value of a và b in the equation (5)

(23 + 33) = (2 + 3)(22 – 2✕3 + 32)

Consider LHS first

LHS = (23 + 33)

LHS = (8 + 27)

LHS = 35

Let us consider the RHS

RHS = (2 + 3)(22 – 2✕3 + 33)

RHS = (5)(4 – 6 + 9)

RHS = (5)(7)

RHS = 35

∴ LHS = RHS

### Refer more

Bạn đang xem: A cube minus b cube formula

5 (6)

Book a miễn phí Class

Relevant Subjects

PhysicsChemistryBiology
MathsScienceGK
JEENEETCommerce
English

Similar Questions

LCM of 42 and 63LCM of 21 và 35LCM of 5 & 25LCM of 50 and 60LCM of 9 & 21LCM of 14 and 28LCM of 3, 4 & 6LCM of 64 & 72LCM of 7 and 15LCM of 8 and 13LCM of 6 and 20LCM of 14 & 16LCM of 5, 10, 15 & 20LCM of 3 & 15LCM of 20, 25 and 30LCM of 45 & 60LCM of 15 và 24LCM of 36 and 72LCM of 9 and 18LCM of 15 và 35
Join BYJU'S Learning Program
Grade/ExamClass 1Class 2Class 3Class 4Class 5Class 6Class 7Class 8Class 9Class 10Class 11Class 12IASCATBank ExamGATE

Xem thêm: Thủy Thủ Mặt Trăng Tập 65 Tiếng Việt, Thủy Thủ Mặt Trăng Tập 65

Submit

COURSES
EXAMSCLASSES
EXAM PREPARATIONRESOURCES